Remediation on underground water pollution using Fenton Oxidation Method - Chok, J.C. (Institute of Physics Publishing, 2020)
Fenton oxidation, one of the advanced oxidation processes (AOP), has high efficiency in the eradication of total petroleum hydrocarbon (TPH), including those persistent organic compounds, with minimal time. Fenton oxidation is employed for further study in the remediation of hydrocarbon-contaminated groundwater sample collected from site. In this study, the efficiency of Fenton Oxidation is investigated toward the degradation of hydrocarbon in groundwater samples. The percentage removal of hydrocarbon, in terms of chemical oxygen demand (COD) in different operating condition for Fenton oxidation of contaminated groundwater was determined. The treatment parameters were selected by carrying out Factorial Design in which pH 3 to 6, concentration of hydrogen peroxide 0.01 mg/L to 0.1 mg/L, concentration of ferrous ions 0.01 mg/L to 0.5 mg/L, and Reaction Time 30 minutes to 120 minutes were proven to be significant model terms. Â© Published under licence by IOP Publishing Ltd.